Examining the “I” in Team: A Longitudinal Investigation of the Influence of Team Narcissism Composition on Team Outcomes in the NBA - Grijalva, Emily; Maynes, Timothy D.; Badura, Katie L.; Whiting, Steven W. (Academy of Management Journal, 2020)
Previous research has shown that narcissism is unrelated to job performance, yet this individual-level effect may be underestimating narcissism’s wider influence on organizational performance. To assess this possibility, we draw on social exchange theory and the agency model of narcissism to investigate how team narcissism composition affects team coordination and performance. Our model was tested using game-level longitudinal data from National Basketball Association teams. Teams with higher mean and maximum levels of narcissism as well as higher narcissism members in core roles (i.e., central and influential roles) had poorer coordination and in turn performance than teams with lower levels. In addition, having higher team familiarity amplified the effects of narcissism for team mean and core role narcissism. The nature of the observed interaction, however, was surprising. Originally, we hypothesized that narcissism would lead to greater decrements in coordination as familiarity increased. Instead, we found that teams with higher mean and core role narcissism maintained the same levels of coordination over time, whereas teams with lower narcissism experienced improvements in coordination. Thus, team-level narcissism appears to prevent teams from capitalizing on normative coordination gains that occur as familiarity increases. These results underscore the importance of considering narcissism when forming teams.